Socio-demographic And Household Sanitation Factors Affect the Quality of Life - Yuniati, Faiza (Journal of Applied Nursing and Health, 2024)
Background: In any society, it is widely accepted that the productive age population's Quality of life (QoL) determines the nation's development. As Indonesia is a developing country, an assessment of the QoL of this group needs concern. Empirical studies have found various factors related to quality of life. However, ecological theory states that environmental factors, including household factors, influence individuals. This study investigates factors associated with the quality of life among productive ages in the general population, including individual factors and home sanitation. Methods: A population-based cross-sectional study was carried out in 23 provinces in Indonesia.  The modified 38-item Indonesia Family Life Survey (IFLS) questionnaire measured quality of life. The total number of productive age people aged 15-64 was 14953 subjects, and 6806 households were used as the population. Determinant factors tested in this study are socio-demographics (age, gender, education, marital status, and primary activity in the past week) and home sanitation.  Data analysis was conducted using multilevel logistic regression. Results: 50.96% (7.620) of productive age have a good quality of life. The study confirmed that age, gender, marital status, education, and primary activity were significant to the QoL. The main finding of this study was that home sanitation had a contextual effect on productive age’s quality of life (ICC = 32.4%, CI = 0.289 – 0.520). Conclusion: Investigation of essential factors related to QoL determines appropriate policy programs and interventions in an effort to improve quality of life. Evaluation of quality of life should concern home sanitation. Sanitation Affects broader aspects of physical and mental health.